Selection Of Tomato Fruits by Color and Size Based on Arduino - Faisal Baharudin Alamsah; Syamsudduha Syahrorini (Procedia of Engineering and Life Science, 2022)
Human life relies heavily on agriculture. To fulfill the needs of human life every day, the process of planting, land, and harvest is fast. Short time and limited power are challenges that farmers should face. Similarly, the problem faced by tomato farmers is that they should be sorting tomatoes based on their level of maturity. The tomato farmers should be sorted by maturity level. The issue is a system of tomato partitioning based on maturity level. The purpose of this research is to design a tool to build the maturity of tomato fruit using Arduino. The tools used are color sensors TCS3200, HC-SR04 Ultrasonic, servo motors, and DC motors. The sorting system is designed using the principle of detecting red green blue (RGB) values of tomato fruit using color sensors. After that, the next system streams the tomatoes to the container according to the level of the decline by opening and closing the portal that is connected to the servo motor. The Portal leads to a ripe container if the fruit is ripe and vice versa if raw fruit leads to a raw container. Results obtained that the sorting tool is able to give a success rate of 90% in distinguishing ripe tomatoes ready to harvest (basil) from raw fruit (green).